2001
DOI: 10.1007/s004420000525
|View full text |Cite
|
Sign up to set email alerts
|

Experimental increase of predation risk induces breeding dispersal of Tengmalm's owl

Abstract: Nest predation and its avoidance are critical components of an individual's fitness and play an important role in life history evolution. Almost all studies on this topic have been observational, and thus have not been able to separate the effects of individual quality, habitat selection and predation risk of given nest sites from each other. More experimental studies on nest predation and breeding dispersal, therefore, are needed to avoid confusing interpretations of the results. In western Finland, pine mart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…Evidence that predators have indirect effects that operate at the regional scale through prey habitat selection (Resetarits & Binckley 2009) and by driving prey dispersal (Weisser et al 1999;Hakkarainen et al 2001;Cronin et al 2004; this study) is accumulating. Evidence of indirect effects operating at a metacommunity scale suggest that understanding community structure requires a broader view of species interactions that encompasses interactions operating across habitats, even when one member of the interacting pair is restricted to only one habitat.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Evidence that predators have indirect effects that operate at the regional scale through prey habitat selection (Resetarits & Binckley 2009) and by driving prey dispersal (Weisser et al 1999;Hakkarainen et al 2001;Cronin et al 2004; this study) is accumulating. Evidence of indirect effects operating at a metacommunity scale suggest that understanding community structure requires a broader view of species interactions that encompasses interactions operating across habitats, even when one member of the interacting pair is restricted to only one habitat.…”
Section: Discussionmentioning
confidence: 86%
“…Only a few studies have found that predators affect movement among habitats across a discontinuous landscape, and none of these is in aquatic habitats. For example, predation risk from ladybirds increases the production of dispersal morphs in pea aphids (Acyrthosiphon pisum; Weisser et al 1999), and in a few cases, predator presence in a patch results in emigration from that patch (Hakkarainen et al 2001;Cronin et al 2004). In these cases, risk was considered as a binary effect, predators were either present or absent, rather than a continuous variable, despite evidence that the effect of predators on movement within a habitat can be sensitive to the level of predation risk an individual experiences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nest predation is a major cause of reproductive failure in birds (e.g., Martin 1995), and observational and experimental studies have found nest losses due to predators to result in increased breeding dispersal rates (Forero et al 1999;Hakkarainen et al 2001; also see Hoover 2003). Roos and Pärt (2004) recently suggested predation risk to influence habitat selection in the red-backed shrike because changes in the spatial distribution of magpie and hooded crow Corvus corone cornix nests affected the spatial patterns and dynamics of territory occupancy in their redbacked shrike population.…”
Section: Predation Riskmentioning
confidence: 99%
“…Experimental and observational evidences suggest that nest predation can cause breeding dispersal (Dow and Fredga 1983;Haas 1998;Forero et al 1999;Hakkarainen et al 2001). Breeding sites should therefore be selected to minimize predation risk, which has been shown in redbacked shrikes (Roos 2002;Roos and Pärt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, these behavioural features are not useful in unpredictable environments. High fidelity also involves the costs of ectoparasitism (Møller 1989, Stanback & Rockwell 2003 or nest predation (Sonerud 1985, Hakkarainen et al 2001. In addition to site fidelity, mate fidelity occurs in some bird species, where they tend to breed with the same mate in the breeding colony.…”
Section: Introductionmentioning
confidence: 99%